Conceptual framework of open and distance learning (ODL) for studio-based architectural design courses / Siti Hasniza Rosman, Suhana Ismail and Abdul Hadi Nawawi - Rosman, Siti Hasniza; Ismail, Suhana; Nawawi, Abdul Hadi (UiTM Press, 2023)
In March 2020, distance education was enforced as a proactive procedure to diminish the spread of the coronavirus. As a result, instructors of advanced and basic design courses were obligated to teach remotely. The emerging virtual studio culture and the unplanned experience need assessment and evaluation, as they may mark a shifting momentum to develop architecture education in unprecedented ways. A large body of research on online education has paid immense attention to the definition of distance and online learning, their types, and their efficiency. The aim of the research is to propose a conceptual framework of open and distance learning (ODL) for studio-based architectural design courses. This research explores various aspects that contribute to the success factors of ODL for studio-based architectural design courses which then forms the fundamentals to develop the conceptual framework of ODL for studio-based achitectural design courses to improve the quality of teaching and learning process. This research is significant in enhancing the effectiveness of ODL and the teaching and learning of studio-based architectural design courses. This research will use a content analysis method approach from literature review study to identify the important aspects and success factors for studio-based architectural design courses. The research will contribute in developing a model to enhance teaching and learning experience through the ODL approach in the studio-based architectural design courses where high focus interactivity between teachers and learners is inherently unique. Overarchingly, this research provides insights on ODL as a future direction in teaching architecture.